Intervention Compliance of Diet and Fluids to Interdialytic Weight Gain in Patients with Chronic Kidney Disease Undergoing Hemodialysis: A Systematic Review - Aprilia Safaroni Roni (Babali Health, 2023)
ABSTRACT Background: Increased fluid as manifested by weight gain in patients with chronic kidney failure hemodialysis programs have a risk impact on fluid accumulation, cardiovascular disorders, hypertension, cognitive impairment, increased hospital stay and death. The low adherence to the diet program is one of the factors causing the interdialyst weight gain value to increase. Objective: To find out the interdialyst weight gain intervention that has been carried out in previous research to improve diet adherence in chronic kidney failure patients with a hemodialysis program. Method :This study studied literature using the PRISMA method, search techniques using PICO from the PuBmed database, Google Scolar, ProQuest, Science Direc, SAGE journals with the keywords chronic kidney failure, hemodialysis, interdialyst weight gain, diet adherence with established inclusion and inclusion criteria. Assess and analyze the quality of the methodology in each study using The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for quasi-experimental. Results: Of the 10 articles reviewed, the journal quality analysis uses analysis from The Joanna Briggs Institute (JBI) according to the criteria of at least 50% meeting the critical appraisal criteria which are then included in the data synthesis. Those 10 articles in the last screening achieved scores higher than 50%. It was found that the interdialyst weight gain intervention proved to be influential in increasing the diet adherence of chronic kidney failure patients with the hemodialysis program. The form of this intervention is fluid management calendar IDWG calculator,smartphone-based health education and reminders. Conclusion: the value of interdialyst weight gain is influenced by dietary adherence in chronic kidney failure patients. Family support is expected to play an active role in dietary compliance, knowledge level, activity control and thirst can be managed properly so that the interdialyst weight gain remains within normal limits.